CLINICAL COURSE AND OPTIMIZATION OF DENTAL MANAGEMENT OF ALVEOLITIS IN CHILDREN WITH TYPE 1 DIABETES MELLITUS - Zebo Gulboeva (Modern American Journals, 2025)
Alveolitis is one of the most frequent inflammatory complications following tooth extraction in pediatric dental practice. In children with type 1 diabetes mellitus, the course of alveolitis is characterized by prolonged inflammation, delayed wound healing, and a high risk of recurrent complications. These features are primarily associated with chronic hyperglycemia, microcirculatory impairment, immune dysfunction, and altered reparative processes. Conventional dental treatment approaches that are effective in somatically healthy children often fail to provide stable clinical outcomes in diabetic patients. The present article analyzes the clinical characteristics of alveolitis in children with type 1 diabetes mellitus and substantiates optimized dental management strategies aimed at improving healing outcomes and preventing recurrences. The results highlight the importance of an individualized and interdisciplinary approach to dental care in this group of patients.
Keywords: Alveolitis, type 1 diabetes mellitus, children, dental management, wound healing.